Arranjos e improvisações para contrabaixo sem acompanhamento em Dave Holland Solo at JazzBaltica 2003 - Pablo Camisão Melo de Souza (2023)
This thesis is a case study on British double bassist Dave Holland’s performance practices as observed in the arrangements and improvisations present in five tracks for double bass without accompaniment contained in the primary source, which is comprised of the video recording of the concert Dave Holland Solo at JazzBaltica 2003. Firstly, Holland’s historical, biographical and social contexts (GRIDLEY, 2009) are reviewed through published interviews, articles in journals, and books. Then, the theoretical references related to musical analysis and music theory (GRELA, 1992; LEVINE, 1995; TUREK, 2007; MED, 1996), improvisation (COKER, 1989; MARTIN, 1996; SANTIAGO, 2006), and rhythm (COHEN, 2007; GAULDIN, 2004; HOENIG; WEIDENMULLER, 2009; PAULI; PAIVA, 2015) are discussed. Finally, Holland’s relevant aspects of arrangement, interpretation, and improvisation on the double bass were selected, analyzed, and presented (BORÉM, 2016) through musical examples constituted by MaPAs (map of audio-visual performance), EdiPAs (edition of audio-visual performance) and thorough transcriptions in EdiPs’ format (performance edition) (BORÉM, 2018 e 2016). Several arrangement and improvisation elements are recognized, discussed and ilustrated as Hollands’ stilistic traits on the double bass: dramatic devices, melodic harmonization on the double bass, fingering patterns, traditional and extended techniques, models of scalar-intervalic improvisation, motivic and thematic improvisation, licks, pathways, CESH, inside-outside approaches, exposition- development-grouping of motives, rhythmic shifts, metric shifts, superimposed metric and change of metrics.